INTERACTIVE METHODS OF TEACHING PRACTICAL EXERCISES IN HIGHER EDUCATIONAL INSTITUTIONS (Journal of Universal Science Research, 2023)
This article presents interactive methods for conducting practical classes in higher educational institutions. At the same time, all methods and directions for conducting practical and laboratory classes with students studying in higher educational institutions are shown.